Pengembangan Wakaf Produktif Berbasis Pesantren Ditinjau dengan Analisis SWOT - Wiwik Erik Setiawan; Yudianto Achmad; MH Ainulyaqin; Achmad, LI; S Edy (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to determine the development of Islamic boarding school-based productive waqf, reviewed using a SWOT analysis. This research uses a qualitative approach, with data collection methods in the form of interviews with informants, direct observation at the Albinaa Islamic boarding school, and study of related literature. The research results showed that in terms of strength, the development of Albinaa's productive waqf has been good considering that at the age of three years Bina Enterprise already has various business units such as: Al Binaa Shop, Bina Resto, Bina Tour, Binaa Food Online, "Asshafa" Beverage Products, School Canteen , Manna Bakery, Al Binaa Inn, Al Bina Farm, Binaa Mart and Bina Finance, Barbershop. In terms of weaknesses, Albinaa does not yet have human resources who are experts in the required fields, there are differences in viewpoints from the management due to obstructive policies, support in developing productive waqf is still lacking. In terms of opportunities, Albinaa has a very large number of students, guardians of students, congregations who have great potential to become customers of Albinaa products. In terms of threats, Albinaa's competitiveness is not yet strong against foreign brands that have already entered the market and are already well established.